The New Detection Method of Ovarian Follicle Development Using Digitized Wide Area Measurement - Noviyanti, Noviyanti; Yueniwati, Yuyun; Rahardjo, Bambang; Mintaroem, Karyono; Khristian, Erick (Open Access Macedonian Journal of Medical Sciences, 2021)
METHODS: The research method used in this research was experimental laboratory with pre-and posttest only control group design. RESULTS: The result shows that the extradiol level which has range of 26.30–31.03 from 28 experimental animals measured, this showed more measurement diameter which has not had measurement addition compare with the wide percentage of measurement. The result shows strong correlation between digitalized measured wide follicles to the changing of estradiol level with value of 0.453. The result of comparation between estradiol level and measured diameter shows weak correlation. This shows that manual measurement of follicle diameter still weak to the changing of estradiol level. CONCLUSION: There is strong correlation between measured wide area follicle used ImageJ applications to the changing of estradiol level compare to the measurement of follicle diameter.